Developing Scientific Writing of Lower Secondary Students through Inquiry and Science Writing Heuristic Learning - Nuntasane, Jirun; Tawnonngiew, Bungorn; Nuangchalerm, Prasart (Jurnal Penelitian dan Pembelajaran IPA, 2020)
This action research aims to develop scientific writing of lower secondary students through inquiry and science writing heuristic learning. Participants were 15 of grade 9 students from one school in Sisaket province, Thailand. Ten lesson plans including 15 hours, a scientific writing assessment form, and scientific writing interviewing form were employed for research instruments. Findings revealed that each spiral was 66.67%, 73.33%, and 100% of students who pass in scientific writing as following. That is could be discussed and promoted in the science classroom. Students need to be more improved their writing skills relevant to science.